A Narrow‐Bandgap n‐Type Polymer with an Acceptor–Acceptor Backbone Enabling Efficient All‐Polymer Solar Cells. Issue 43 (21st September 2020) - Sun, Huiliang; Yu, Han; Shi, Yongqiang; Yu, Jianwei; Peng, Zhongxiang; Zhang, Xianhe; Liu, Bin; Wang, Junwei; Singh, Ranbir; Lee, Jaewon; Li, Yongchun; Wei, Zixiang; et al.
Abstract: Narrow‐bandgap polymer semiconductors are essential for advancing the development of organic solar cells. Here, a new narrow‐bandgap polymer acceptor L14, featuring an acceptor–acceptor (A–A) type backbone, is synthesized by copolymerizing a dibrominated fused‐ring electron acceptor (FREA) with distannylated bithiophene imide. Combining the advantages of both the FREA and the A–A polymer, L14 not only shows a narrow bandgap and high absorption coefficient, but also low‐lying frontier molecular orbital (FMO) levels. Such FMO levels yield improved electron transfer character, but unexpectedly, without sacrificing open‐circuit voltage ( V oc ), which is attributed to a small nonradiative recombination loss ( E loss, nr ) of 0.22 eV. Benefiting from the improved photocurrent along with the high fill factor and V oc, an excellent efficiency of 14.3% is achieved, which is among the highest values for all‐polymer solar cells (all‐PSCs). The results demonstrate the superiority of narrow‐bandgap A–A type polymers for improving all‐PSC performance and pave a way toward developing high‐performance polymer acceptors for all‐PSCs. Abstract : A narrow‐bandgap polymer acceptor L14 with an acceptor–acceptor (A–A) backbone is synthesized, showing lower‐lying frontier molecular orbitals, higher electron mobility, and larger absorption coefficient without sacrificing photovoltage compared to its donor–acceptor (D–A) analog polymer, L11. When applied in all‐polymer solar cells, L14 yields an outstanding efficiency of 14.3%.